(untitled) (Journal of Experimental and Clinical Anatomy, 2003)
The traditional method of teaching and research in Anatomy and Pathology use mainly specimens fixed in formalin and ethyl alcohol for the demonstration of gross tissue specimens. However, some of the limitations as regards preparation, storage, handling and disposal of these specimens have resulted in the introduction of this new method of tissue preservation called plastination which improves the handling, storage qualities and durability of these teaching and research specimens.